Izbrane dobre prakse vrhovnih sodišč držav članic EU in možnosti njihove uporabe v delovnih in socialnih sporih - Rataj, Primož (Delavci in delodajalci, 2017)
The contribution focuses on the possibilities of use of best practices of Supreme courts in labour and social disputes. These practices were identified in the recently published best practices guide. The author deals with the question whether selected best practices contribute to the effectiveness and the quality of judicial decision-making and if so, in what form, especially in comparison with the current established solutions. The attention is predominantly given to the potential improvements with the electronic document management system, through case allocation and notification of parties, with the accessibility of judgments to the public and the cooperation of judges with academia.
Keywords: delovni spor; delovno pravo; Evropska unija; odločanje; reševanje; socialni spor; socialno pravo; sodna praksa; vrhovna sodišča